2017
DOI: 10.1213/ane.0000000000002497
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Opioid-Sparing Modalities in Perioperative Pain Management: Methods to Decrease Opioid Use Postoperatively

Abstract: There is an epidemic of opioid use, abuse, and misuse in the United States, which results in significant morbidity and mortality. It may be difficult to reduce perioperative opioid use given known acute surgical trauma and resultant pain; however, the discrete and often limited nature of postoperative pain also may make management easier in part by utilizing nonopioid modalities, such as regional anesthesia/analgesia, and multimodal analgesia, which may decrease the need for powerful opioids. This article revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
141
0
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 260 publications
(150 citation statements)
references
References 125 publications
2
141
0
7
Order By: Relevance
“…Back in 2010, the Italian Society of Anesthesia, Analgesia and Intensive Care (SIAARTI) already recommended the adoption of multimodal analgesic strategies and underlined the importance of their adjustment to fast-track surgical settings (10). Recent reviews on analgesic care in ERAS protocols report the same concept, highlighting the necessity of combining systemic and loco-regional analgesia to favour opioidsparing strategies (4,5,11). The latter goal is extremely important, to minimize not only the side effects of this pharmacological class, but also the risk of respiratory complications of patients undergoing thoracic surgery.…”
Section: Multimodal Analgesia Strategymentioning
confidence: 99%
“…Back in 2010, the Italian Society of Anesthesia, Analgesia and Intensive Care (SIAARTI) already recommended the adoption of multimodal analgesic strategies and underlined the importance of their adjustment to fast-track surgical settings (10). Recent reviews on analgesic care in ERAS protocols report the same concept, highlighting the necessity of combining systemic and loco-regional analgesia to favour opioidsparing strategies (4,5,11). The latter goal is extremely important, to minimize not only the side effects of this pharmacological class, but also the risk of respiratory complications of patients undergoing thoracic surgery.…”
Section: Multimodal Analgesia Strategymentioning
confidence: 99%
“…Multimodal pain management focuses on the combination of several analgesic agents and techniques to modulate pain at both central and peripheral sites, thereby enhancing analgesia and lessening opioid use and opioid‐related adverse effects . However, peripheral nerve blockade has been to play the major role in postoperative multimodal pain regimens .…”
Section: Discussionmentioning
confidence: 99%
“…Our primary outcome showed that pretreatment with peripheral nerve blockade was superior to pretreatment with periincisional LA infiltration on significant low-pain intensity and low-impact Multimodal pain management focuses on the combination of several analgesic agents and techniques to modulate pain at both central and peripheral sites, thereby enhancing analgesia and lessening opioid use and opioid-related adverse effects. 8,9 However, peripheral nerve blockade has been to play the major role in postoperative multimodal pain regimens. 10,11 The conventional nerve block techniques for forefoot surgery are popliteal sciatic nerve block 12 or ankle nerve blocks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is growing interest in opioid-sparing methods in perioperative pain management, given an ongoing epidemic of opioid use and misuse that is causing significant morbidity and mortality 1. While misuse occurs more frequently among chronic pain patients, the perioperative period is often the patient’s first exposure to these medications 2…”
Section: Introductionmentioning
confidence: 99%